The "Misura Aurea" of Italian Cooking: Defining Authentic Foods for Locals and Tourists in Postwar Italy, 1953 to 1974. Issue 3 (2nd September 2019) - Gray, Melissa
ABSTRACT: The growth of postwar mass tourism in Italy drove the assertion of Italian identity through so- called authentic foods. I follow the actions of culinary societies alongside private and government tourism promoters, arguing that the history of "true" Italian food reveals the contradictory results of globalization as it related to reactions to Americanization. Discourses of genuine Italian cuisine managed by the Accademia Italiana della Cucina in particular relied on the market as a site of cultural production and borrowed its logic of standardization to guarantee quality. Postwar efforts codifying Bologna's traditional cuisine and promoting it as a culinary destination demonstrates the challenge of democratizing discourses of food and identity and affirm the role negotiations of power have played in defining Italian food.